2021
DOI: 10.3389/fphar.2021.610158
|View full text |Cite
|
Sign up to set email alerts
|

Biejiajian Pill Inhibits Carcinogenesis and Metastasis via the Akt/GSK-3β/Snail Signaling Pathway in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is among the most usual cancers globally. In China, Biejiajian pill (BJJP), Traditional Chinese Medicine clinical prescription, is broadly utilized for the prevention and therapy of HCC. However, the mechanisms by which BJJP exerts its effects on the prevention of tumor invasion and metastasis are still largely unknown. In this study, in vitro multiple hepatic cancer cell lines and an in vivo xenograft mice model were used to validate the preventive effects and molecular mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…BJJP is a canonical formula from "The Synopsis of Golden Chamber" that is made up of 23 ingredients and is widely used in TCM for the treatment of HCC. A previous study by our research group showed that the main components of BJJP were wogonin, zerumbone, ursolic acid, resveratrol and 6gingerol (Sun et al, 2021), all of which have been reported to regulate tumor immunity. Notably, wogonin was shown to have immune-modulatory effects as it regulated the function of effector T cells (Fan et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…BJJP is a canonical formula from "The Synopsis of Golden Chamber" that is made up of 23 ingredients and is widely used in TCM for the treatment of HCC. A previous study by our research group showed that the main components of BJJP were wogonin, zerumbone, ursolic acid, resveratrol and 6gingerol (Sun et al, 2021), all of which have been reported to regulate tumor immunity. Notably, wogonin was shown to have immune-modulatory effects as it regulated the function of effector T cells (Fan et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…Previous study found that BJJP exerted a tight inhibitory influence on the progression of HCC by the inhibition of EMT, which plays important role in hepatocellular carcinoma (Li et al, 2021;Sun et al, 2021). It was reported that EMT signature is inversely associated with T-cell infiltration, which promote tumor cell to escape from immune system defense (Chae et al, 2018;Aghajani et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Biejiajian pill (BJJP) originated from Synopsis of Golden Chamber, a traditional Chinese medicine clinical prescription, is broadly utilized for the prevention and therapy of hepatocellular carcinoma [5], so the research on BJJP mainly focused on digestive disease. In recent years, some studies have found that BJJP has a significant effect on diabetic atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%